(3JOHjQ GdeJhMOs - (3GHf HGLI , CHh HcQ Hf GdUGFZ GdSQbSWj,J (B533 (3g` s
(3ChdgG (B:s
(3bGd CHhHcQ GHf GdUGjZ daXI GdJOHjQ JbGd Yf JQJjH CaYGd s
(3BNQgG (B:s
(3aGdEfSGf ef CYGLjH GdWHjYI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B332 - (3U(B345s
(3gPg gi GdebGdI GdChdi ef cJGH JOHjQ GdeJhMOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B63s
Keywords: (3GdadSaI hGdefWbs